Novel background calibration algorithm for image in non-uniform illumination field. (May 2015) - Wang, H. F.; Wang, G. P.; Wang, X. Y.; Wang, B. J.; Zhao, X. D.
Abstract : For the purpose of solving the high quality required in some image based measurement systems, a new calibration algorithm for a non-uniform illumination field image is proposed on the basis of some existing algorithm. In this algorithm, by analysing the characteristics of the potential function for target detection, a new potential function for target detection was designed. A measurement function for standardisation of variety was deduced thereafter. After that, the mapping function from the original image to the background calibration image was given. Numerical simulations showed that the proposed algorithm can restrain the non-uniform background illumination field and calibrate the strong fluctuant background of the illumination field image and thus improve the quality of the image. Meanwhile, the algorithm is simple to carry out and very suitable in practice.